(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
As known the Weak Nuclear Force or Weak Interaction(WI) acts between quarks (Qs) and leptons. The action of the WI is mediated by highly massive gauge bosons. How does a nuclear Q emit such a massive particle, approximately 16000 or 40000 times its mass? Who provides so much energy to a up Q or a down Q? However, it must be considered that according to Quantum Mechanics it is possible to loan temporarily some energy, but to a precise and binding condition, established by the Uncertainty Principle: the higher the energy borrowed, the shorter the duration of the loan. Our calculations show that the maximum distance these bosons can travel, i.e. the upper limit of their range, corresponds to 1.543×10-15 [cm] for particles W+ and W- and 1.36×10-15[cm] for Z° particles.